An analysis of whether privately owned financial planning practices are transitioning to fully independent advice providers - Darren Pawski; Robert Powell; Anna Golab (Journal of Risk and Financial Management, 2022)
In Australia, there are over 20,000 financial advisers, with only 1% registered as independent financial advisers. This study investigates why there has been no significant transition to independent advising. The importance of the study is underlined by the substantial losses suffered by thousands of consumers from advice that has been found to be influenced by conflicts of interest. Using a qualitative technique, the study undertook exploratory semi-structured interviews among financial advisers. The study found that over 90% of privately owned advisers will not be transitioning to independent advising due to the belief that clients will not pay fees for insurance advice. The study finds strong evidence that the affordability of paying fees for insurance advice arguably outweighs the conflicts of interest associated with non-independent insurance advice.
Keywords: 650; conflict of interest; financial advice; financial planning; independent financial adviser